Proteomic Analysis of Early HIV-1 Nucleoprotein Complexes - Schweitzer, Cameron J. (2013)
After entry into the cell, the early steps of the human immunodeficiency virus type 1 (HIV-1) replication cycle are mediated by two functionally distinct nucleoprotein complexes, the reverse transcription complex (RTC) and preintegration complex (PIC). These two unique viral complexes are responsible for the conversion of the single-stranded RNA genome into double stranded DNA, transport of the DNA into the nucleus, and integration of the viral DNA into the host cell chromosome. Prior biochemical analyses suggest that these complexes are large and contain multiple undiscovered host cell factors. In this study functional HIV-1 RTCs and PICs were partially purified by velocity gradient centrifugation and fractionation, concentrated, trypsin digested, and analyzed by LC-MS/MS. A total of seven parallel infected and control biological replicates were completed. Database searches were performed with Proteome Discoverer and a comparison of the HIV-1 samples to parallel uninfected control samples was used to identify unique cellular factors. The analysis produced a total data set of 11,055 proteins. Several previously characterized HIV-1 factors were identified, including XRCC6, TFRC, and HSP70. The presence of XRCC6 was confirmed in infected fractions, and shown to be associated with HIV-1 DNA by immunoprecipitation-PCR experiments. Overall, the analysis identified 94 proteins unique in the infected fractions and 121 proteins unique to the control fractions with ≥ 2 protein assignments. An additional 54 and 52 were classified as enriched in the infected and control samples, respectively, based on a three-fold difference in total Proteome Discoverer probability score. The differential expression of several candidate proteins was validated by Western blot analysis. This study contributes additional novel candidate proteins to the growing published bioinformatic data sets of proteins that contribute to HIV-1 replication.